2020
DOI: 10.9778/cmajo.20190186
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic features of medical emergencies in remote First Nations in northern Ontario: a cross-sectional descriptive study using air ambulance transport data

Abstract: A lmost all residents of Ontario, Canada live within 30 minutes of an emergency department. 1 However, for about 25 000 Ontarians living in remote commun ities, accessing a doctor in an emergency department requires flying in a plane or helicopter. 1 Patients in these northern com munities access medical care through a local nursing station, with intermittent incommunity physician coverage. Patients with highacuity conditions are transported from remote com munities to hospital by Ornge, the provincial medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…The included studies specifically targeted the following diseases of focus: CVD; n = 8); heart health (n = 5); hypertension (n = 2); stroke (n = 2); coronary artery disease (n = 2); rheumatic fever (n = 1); or a combination of multiple chronic diseases (eg, CVD, diabetes; n = 1). 2 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 The aim of each study varied, in reflection of the following categories (note that some studies were identified as falling within multiple categories; Table 2 ): risk factor—understand discrepancies in or origins of heart health (n = 10); intervention—design/implementation of program or strategy (n = 9); and heart health management—Indigenous and/or Western approaches to manage heart health (n = 8). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The included studies specifically targeted the following diseases of focus: CVD; n = 8); heart health (n = 5); hypertension (n = 2); stroke (n = 2); coronary artery disease (n = 2); rheumatic fever (n = 1); or a combination of multiple chronic diseases (eg, CVD, diabetes; n = 1). 2 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 The aim of each study varied, in reflection of the following categories (note that some studies were identified as falling within multiple categories; Table 2 ): risk factor—understand discrepancies in or origins of heart health (n = 10); intervention—design/implementation of program or strategy (n = 9); and heart health management—Indigenous and/or Western approaches to manage heart health (n = 8). …”
Section: Resultsmentioning
confidence: 99%
“… 2 , 14 , 25 Several studies described stories in which, owing to racial biases, individuals were provided with dismissive clinical interactions in the emergency department (eg, being prescribed antibiotics for a heart attack) or were forbidden to embrace their cultural values (eg, were unable to bring traditional foods to hospitalized community members), creating a sense of emotional harm when seeking care and support. 2 , 25 , 26 , 27 , 28 , 29 , 30 …”
Section: Resultsmentioning
confidence: 99%
“…For example, in Northwest Ontario, approximately 10% of air ambulance flights are for cardiovascular emergencies. 47 …”
Section: Discussionmentioning
confidence: 99%
“…Many patients require the initiation and coordination of medical transportation from their remote community. A recent analysis of regional emergency air transportations ('medevacs') document that 54% of cases from the 26 fly-in First Nations communities in northwest Ontario were directed to SLMHC (mean annual number of transports 1146) [21]. Of these, 7.5% were for toxicologic emergencies and 11.3% were for accidental/nonaccidental trauma.…”
Section: Comparison To Previous Studiesmentioning
confidence: 99%